2019
DOI: 10.1111/1365-2664.13514
|View full text |Cite
|
Sign up to set email alerts
|

Do introduced apex predators suppress introduced mesopredators? A multiscale spatiotemporal study of dingoes and feral cats in Australia suggests not

Abstract: 1. The role of apex predators in structuring ecosystems through the suppression of mesopredator activity and abundance is receiving increasing attention, largely due to the potential benefits for biodiversity conservation. In Australia, invasive mesopredators such as feral cats (Felis catus) have been identified as major contributors to Australia's mass mammal extinctions since European arrival. The introduced dingo (Canis familiaris) has been proposed as a novel way to suppress the impacts of feral cats, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
(69 reference statements)
4
27
1
Order By: Relevance
“…(2020) in western Victoria, but contrasts with the results of Fancourt et al. (2019) that found little diurnal activity by feral cats during winter months. Elsewhere, feral cat diel activity has also been shown to vary with seasonality (Wang and Fisher 2012).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…(2020) in western Victoria, but contrasts with the results of Fancourt et al. (2019) that found little diurnal activity by feral cats during winter months. Elsewhere, feral cat diel activity has also been shown to vary with seasonality (Wang and Fisher 2012).…”
Section: Discussioncontrasting
confidence: 67%
“…2017 a , Fancourt et al. 2019). The analytical framework presented here can readily be applied to landscapes with dingoes, foxes, and cats, and inform the current debate, and subsequently guide management options for introduced predators throughout Australia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…dingo, jackal Canis spp.) provide a valuable test of MR as a working ecological theory that is testable across systems with different ecological contexts (Fancourt et al 2019). Further, such information could be vital for creating informed management plans for mesopredator species and for the critical evaluation of the goals and effectiveness of ongoing widescale control or eradication programmes (Gompper 2002, Gehrt & Clark 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Foxes and cats can have major impacts on medium‐sized mammals in some ecosystems (Kinnear et al 1988; Short & Smith 1994; Kinnear et al 2002; Doherty et al 2015; Radford et al 2018), but because they were rarely detected in burn blocks following prescribed burns, these mesopredators would have little impact at our sites. Some studies have reported that the Dingo populations may have a suppressive effect on mesopredators including cats and foxes (Johnson & VanDerWal, 2009; Brook et al 2012); however, see Fancourt et al (2019). This may explain the negligible activity of foxes and cats in our study; however, our data did not allow exploration of these relationships.…”
Section: Discussionmentioning
confidence: 99%